A bibliometric analysis on the tribological and physicochemical properties of vegetable oil--based bio-lubricants (2010--2021) - Lee, Chiew Tin; Lee, Mei Bao; Mong, Guo Ren; William Chong, Woei Fong (Springer Nature, 2022)
Vegetable oil–based bio-lubricants possess potential as an alternative to mineral oil–based lubricants due to their biodegradability and renewability. However, a detailed examination of the publication focus, trend, and future direction related to these bio-lubricants’ tribological and physicochemical properties is scarce. Therefore, the study presents a bibliometric analysis of vegetable oil–based bio-lubricant. One hundred sixty-five publications were extracted from Web of Science (WoS) from 2010 to 2021. During this period, the total citation was 2,240, recording an average citation per publication of 13.58. Proceedings of The Institution of Mechanical Engineers, Part J: Journal of Engineering Tribology was the top productive journal, publishing 10.3% of the publications selected on the studied topic. From 2010 to 2021, India was the most productive country working on bio-lubricants due to its abundance of coconut products, followed by Malaysia due to its abundance of palm products. The keyword analysis indicated that a significant amount of work emphasised the derivation of bio-lubricants with an increasing shift towards tribological performance characterisation. From the analysis, palm is the most studied bio-lubricant, followed by castor oil. The reported viscosity and viscosity index values cover an extensive range, allowing these bio-lubricants to be adopted for a wide range of applications. For different vegetable oil–based bio-lubricants, the coefficient of friction is reported from 0.001 to 0.78, with the wear scar diameter being reported from 0.075 μm to 4.59 mm. Even though these bio-lubricants’ friction and wear performances can be tabulated, the dataset is still unreliable for lubricant-selection purposes because of the varying test conditions. Such a scenario also limits the ability to correlate the role of fatty acid composition in the vegetable oil–based bio-lubricants in fulfilling their various application-specific potentials. Therefore, this study recommends that a unified correlation between the fatty acid composition and its tribological performance be attained consistently to better elucidate the potential of vegetable oil–based bio-lubricants.